2018
DOI: 10.1158/0008-5472.can-17-3006
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the Wnt/β-Catenin Pathway Overcomes Resistance to Enzalutamide in Castration-Resistant Prostate Cancer

Abstract: Enzalutamide is a second-generation nonsteroidal antiandrogen clinically approved for the treatment of castration-resistant prostate cancer (CRPC), yet resistance to endocrine therapy has limited its success in this setting. Although the androgen receptor (AR) has been associated with therapy failure, the mechanisms underlying this failure have not been elucidated. Bioinformatics analysis predicted that activation of the Wnt/β-catenin pathway and its interaction with AR play a major role in acquisition of enza… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
100
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 130 publications
(101 citation statements)
references
References 37 publications
1
100
0
Order By: Relevance
“…Whereas LNCaP and C4-2 are enzalutamide-sensitive PCa cells, MR49F and C4-2R cells are enzalutamide resistant but are derived from LNCaP and C4-2, respectively. Upon comparing the RNA profiles of drug-resistant cell lines to their drug-sensitive counterparts, 1268 genes were identified as differentially expressed genes (DEGs) in C4-2R and 903 genes were found as DEGs in MR49F (Supplementary Tables S1A and S1B), which is in agreement with our published results in C4-2R (20). Using KEGG predefined pathway analysis, pathways related to PCa progression were significantly enriched in C4-2R and MR49F ( Fig.…”
Section: Upregulation Of Ar Correlates With An Active State Of Ephb4supporting
confidence: 87%
See 1 more Smart Citation
“…Whereas LNCaP and C4-2 are enzalutamide-sensitive PCa cells, MR49F and C4-2R cells are enzalutamide resistant but are derived from LNCaP and C4-2, respectively. Upon comparing the RNA profiles of drug-resistant cell lines to their drug-sensitive counterparts, 1268 genes were identified as differentially expressed genes (DEGs) in C4-2R and 903 genes were found as DEGs in MR49F (Supplementary Tables S1A and S1B), which is in agreement with our published results in C4-2R (20). Using KEGG predefined pathway analysis, pathways related to PCa progression were significantly enriched in C4-2R and MR49F ( Fig.…”
Section: Upregulation Of Ar Correlates With An Active State Of Ephb4supporting
confidence: 87%
“…Nevertheless, how c-Myc is overexpressed in advanced PCa is not well studied. Our previous publications showed the contribution of β-catenin and PI3K/AKT/mTOR to ADT resistance (20,35). Considering that these two pathways are known to elevate c-Myc (36,37), and EphB4 acts upstream of β-catenin and PI3K/AKT/mTOR (7-9), it is reasonable to extrapolate that EphB4 and c-Myc work as the pivot to control the expression of AR through multiple signaling pathways in enzalutamide-resistant CRPC.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, recent studies have shown that the aberrant activation of the EMT and Wnt/β-catenin pathway also contributes to enzalutamide resistance in prostate cancer ( 105 107 ).…”
Section: Mechanisms Of Resistance To Ar Antagonistsmentioning
confidence: 99%
“…However, how JWXLD alleviates inflammation is still not clear. [42,43]. For clinical application purpose, what are the effects of JWXLD on antitumor efficacy of CPT-11 need be explored more in future.…”
Section: Discussionmentioning
confidence: 99%